Pengaruh Presepsi Harga, Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Kosmetik Pinkflash pada Mahasiswi FEBI UIN SATU Tulungagung - Fristica Emiliani; Muhammad Alhada Fuadilah Habib (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research is underpinned by the price offered by the cosmetic product pinkflash that is relatively cheap, besides that the product has good product quality as well as has an excellent brand image, so this product has become a popular product among teenagers to adult women. The purpose of this research is to (1) determine the impact of price prescription, product quality and brand image simultaneously on the purchase decision of pinkflash cosmetics. (2) To know the influence of pric prescription on the decision of purchase of Pinkflash Cosmetic products. (3) To know how the quality of the product affects the decision on purchase of the pinkflush cosmetic product. This research uses a quantitative approach to the type of research used, which is associative, which explains the relationship between variables. The sample sampling method used in this study is non probability Sampling, with the population being students of UIN ONE Bone who have used or are using pinkflash cosmetic products. The data collection technique used is a questionnaire by giving a written statement to the respondent to be answered. The results were then analyzed using trials in SPSS 16. The results of the research showed that: (1) price prescriptions, product quality and brand image simultaneously and significantly influence the purchase decision of pinkflash cosmetics (2) price prescription does not have a positive influence on the decision of purchase of pinkflash Cosmetics (3) product quality has a positive and significant influence upon the decision to purchase pinkflash cosmetic products (4) brand image has a positively and significant effect on the purchasing decision of pinkflash Cosmetic Products.